Pengaruh Budaya Asing Terhadap Pembentukan Identitas Nasional: Studi Kasus Mahasiswa Umrah Di Tanjung Pinang - Melisa Melisa (Intellektika : Jurnal Ilmiah Mahasiswa, 2025)
the influence of foreign culture on national identity in Indonesia, focusing on students of Raja Ali Haji Maritime University. This study shows that globalization facilitates the entry of foreign cultures that have the potential to erode local cultural values. Through interviews, it was found that students felt both positive and negative impacts of foreign culture, such as increased knowledge of foreign languages and the loss of local cultural characteristics. The author emphasizes the importance of maintaining Indonesian cultural identity amidst the ever- growing flow of globalization.